KONTRIBUSI POWER LENGAN DAN POWER TUNGKAI TERHADAP HASIL LARI SPRINT 100 METER KELAS VII DI SMPN 7 TAPUNG HULU, KABUPATEN KAMPAR - Yoga Yolanda; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research is to find the contribution of arm power and leg power on the result of 100m sprint of 7th Grade in SMPN 7 Tapung Hulu, Kampar Regency. This research was done in October 2020 - August 2021 in SMPN 7 Tapung Hulu, Kabupaten Kampar, meanwhile the population in this research whis is the 7th Graders that consists of 34 students. Sampling technique used in this research was sampling purposive. The samples in this research were male students in 7th grade of SMPN Tapung Hulu, Kabupaten Kampar, which was 20 students. Based on the result of this research that the writer has wrote on the previous bab (aku ragu bab tu inggris e ape wkwk), we can conclude that: 1) Based on the result of arms power's contribution in 100m sprint of 7th Graders in SMPN 7 Tapung Hulu Kabupaten Kampar has contributed 38,81%. 2)Based on the result of leg power's contribution in 100m sprint of 7th Graders in SMPN 7 Tapung Hulu Kabupaten Kampar has contributed 49,81%. 3) There is a contribution of both arm power and leg power in 100m sprint of 7th Graders in SMPN 7 Tapung Hulu Kabupaten Kampar which was 57,76%.Key Word: Arm Power, Leg Power, Sprint Run Result